A Psychological Success Cycle And Goal Setting: Goals, Performance, And Attitudes - Hall, Douglas T.; Foster, Lawrence W. (Academy of Management Journal, 1977)
Based upon a model of the causes and effects of psychological success, the following series of relationships was predicted for participants in a simulated management exercise: goals ? efforts ? performance ? psychological success ? self-esteem ? involvement ? later goals. Two measurements were taken, and the relationships were tested with path analysis and cross-lagged correlations. Except for effort ? performance, significant relationships indicated support for a cyclical model of career development. Correlational causal analyses indicated that good performance leads to increased involvement.